Pandemic Covid-19 Effect on PON Banten 2012 Athlete of Basket Ball Motivation? - Iman Sulaiman; Oktavianus Matakupan (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
This study aims to determine the impact of the covid 18 pandemic on the motivation to practice basketball athletes at PON Banten. The method used in this research is this research is a descriptive study with a survey method, this research was conducted on 26 athletes of Pelatda PON Banten Basketball athletes. The data needed in this study is data in the form of the results of a Likert scale questionnaire, namely the motivation variable for training during covid 19. The results showed that the motivation for training during the covid19 pandemic was that the basketball athletes of Pelatda Pon Banten Putra with the largest frequency were in moderate motivation with a total of 14 athletes with a percentage 54%, followed by high motivation with 19 athletes with a percentage of 35%, and low motivation with only 3 athletes with a percentage of 12%. Research provides an overview of the object of research as it is. To provide an overview of the motivation for training in men's basketball athletes from the Banten Regional Training and it turns out that motivation is really needed for athletes.Key words: Basket Ball, Motivation, Covid 19